Data on correction of pelvic organ prolapse by laparoscopic lateral suspension with mesh: A clinical series - Ruby Martinello (Data in Brief, 2019)
This DIB article provides additional data on laparoscopic lateral suspension with mesh for correcting pelvic organ prolapse. Data come from a multicentric sample of Italian women (https://doi.org/10.1016/j.ejogrb.2019.07.025). Data are collected retrospectively. Descriptive and raw data on surgery and descriptive and raw data on symptoms of pelvic organ prolapse pre-surgery and post-surgery are provided. Kaplan-Meier curves and scores of 7-items King's Health Questionnaire for quality of life assessment are also reported. Keywords: Pelvic organ prolapse, Laparoscopic lateral suspension, Surgical treatment, Mesh